Job Stress and Coping Skills: An Analytical Study with Special Reference to Personality of D.Ed. Teachers: Understanding Job Stress and Coping Skills among D.Ed. Teachers (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The study is to understand, personality of Zilla Parishad D.Ed. teachers, all the aspect and dynamic personality these teachers have. The question how these teachers have to deal with stress and how enjoyable they make their work and life while travelling daily with lot of working stress? How do they fiddle with their stress? Their ways coping stress.